Patterns of Change in ACGME-Accredited Residency Programs and Positions: Implication for the Adequacy of GME Positions and Supply of Physicians in the United States - Holt, Kathleen D. (The Accreditation Council for Graduate Medical Education, 2014)
BACKGROUND: Recent studies suggest that the supply of primary care physicians and generalist physicians in other specialties may be inadequate to meet the needs of the US population. Data on the numbers and types of physicians-in-training, such as those collected by the Accreditation Council for Graduate Medical Education (ACGME), can be used to help understand variables affecting this supply. OBJECTIVE: We assessed trends in the number and type of medical school graduates entering accredited residencies, and the impact those trends could have on the future physician workforce. METHODS: Since 2004, the ACGME has published annually its data on accredited institutions, programs, and residents to help the graduate medical education community understand major trends in residency education, and to help guide graduate medical education policy. We present key results and trends for the period between academic years 2003–2004 and 2012–2013. RESULTS: The data show that increases in trainees in accredited programs are not uniform across specialties, or the types of medical school from which trainees graduated. In the past 10 years, the growth in residents entering training that culminates in initial board certification (“pipeline” specialties) was 13.0%, the number of trainees entering subspecialty education increased 39.9%. In the past 5 years, there has been a 25.8% increase in the number of osteopathic physicians entering allopathic programs. CONCLUSIONS: These trends portend challenges in absorbing the increasing numbers of allopathic and osteopathic graduates, and US international graduates in accredited programs. The increasing trend in subspecialization appears at odds with the current understanding of the need for generalist physicians.